2016
DOI: 10.1007/s11356-016-7297-6
|View full text |Cite
|
Sign up to set email alerts
|

Phalangeal bone anomalies in the European common toad Bufo bufo from polluted environments

Abstract: Every spring, many of amphibians are killed by motor vehicles on roads. These road-killed animals can be used as valuable material for non-invasive studies showing the effect of environmental pollution on amphibian populations. The aims of our research were to check whether the phalanges of road-killed toads may be useful as material for histological analysis, and whether various degrees of human impact influence the level in bone abnormalities in the common toad. We also examined whether the sex and age struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…They found almost no juvenile carcasses, while they were observed in adjacent live population. However, in our study, we focused on breeding migrating population of common toads, therefore we detected only sexually mature individuals (Kaczmarski et al 2016;Hemelaar 1986). Juvenile toads do not migrate to breeding ponds, nevertheless, we cannot exclude the possibility of finding roadkilled young individuals migrating to foraging habitat in different locations.…”
Section: Age Structure Of Live and Road-killed Toadsmentioning
confidence: 99%
See 3 more Smart Citations
“…They found almost no juvenile carcasses, while they were observed in adjacent live population. However, in our study, we focused on breeding migrating population of common toads, therefore we detected only sexually mature individuals (Kaczmarski et al 2016;Hemelaar 1986). Juvenile toads do not migrate to breeding ponds, nevertheless, we cannot exclude the possibility of finding roadkilled young individuals migrating to foraging habitat in different locations.…”
Section: Age Structure Of Live and Road-killed Toadsmentioning
confidence: 99%
“…An hour after dark, we captured by hand all encountered live toads, that crossed the road which intersects their migration routes, and dead ones killed due to collision with vehicles. We determined sex of live and dead individuals directly in the field (according to Kaczmarski et al 2016). We identified males by the occurrence of the nuptial pad, whereas females by ovaries and eggs (dead individuals) and auxiliary also by body size and shape.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that roads can be barriers for different taxa, such as birds, amphibians, reptiles, and mammals (e.g. de Freitas et al , Kaczmarski et al , Kiros et al ), and may have a broad impact on wildlife biodiversity (Ibisch et al ). The loss of individuals due to vehicle collisions may influence the dynamics of populations far from the road (Roger et al , Van Der Ree et al ).…”
Section: Introductionmentioning
confidence: 99%